Gender aspects of urolithiasis development in patients with metabolic syndrome - I. D. Bespalova; V. S. Boshchenko; Yu. I. Koshchavtseva; A. V. Tsoy; A. V. Teteneva; P. E. Mesko; A. I. Karzilov; Ya. V. Porovskiy; E. L. Mishustina; K. F. Tetenev; E. V. Kalyuzhinа; V. V. Kalyuzhin (Бюллетень сибирской медицины)
The review summarizes and analyzes the results of domestic and major foreign studies of recent years concerning gender characteristics of the epidemiology and development mechanisms of metabolic syndrome and urolithiasis as an associated disease. A deep understanding of gender aspects in the pathogenesis of these pathologies can form the basis for development of high-quality diagnostic algorithms and pathogenetically grounded approaches to treatment.